Peningkatan Kemampuan Sosial Emosional Anak Melalui Model Role Playing - Hasan, Haryawati; Sadaruddin, Sadaruddin; Nasaruddin, Nasaruddin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This study aims to improve children's social-emotional skills through the application of the role playing method at Harapan Ibu Halawatul Iman Kindergarten. The social-emotional skills focused on in this study include the aspects of “obeying the rules” and “queuing for turn”. The Classroom Action Study (PTK) method was used in this study with two cycles, each consisting of three meetings. The study subjects were 15 playgroup children aged 3-4 years. Data were collected through observation and field notes, and analyzed utilizing qualitative and quantitative descriptive approaches. The results of the study indicated that the application of role playing was successful in improving children's social-emotional skills, especially in the aspects of obeying rules and queuing for turns. Most children indicated good development, with 40% of children in the Developing As Expected (BSH) category and 40% in the Beginning to Develop (MB) category in terms of obeying the rules. Meanwhile, in the aspect of queuing their turn, 53% of children were in the BSH category and 47% in the MB category. These results indicate that the role playing method is effective in increasing children's social skills, including patience, empathy, and cooperation, which support their emotional development.